A Characterization of Planar Mixed Automorphic Forms - Allal Ghanmi (International Journal of Mathematics and Mathematical Sciences)
We characterize the functional space of the planar mixed automorphic forms with respect to an equivariant pair and given lattice as the image of the Landau automorphic forms (involving special multiplier) by an appropriate isomorphic transform.